Discovery and characterization of a potent and selective EP4 receptor antagonist. Issue 16 (15th August 2015) - Schiffler, Matthew A.; Chandrasekhar, Srinivasan; Fisher, Matthew J.; Harvey, Anita; Kuklish, Steven L.; Wang, Xu-Shan; Warshawsky, Alan M.; York, Jeremy S.; Yu, Xiao-Peng
Graphical abstract